Drug-drug interactions between antiretrovirals and bedaquiline - Pandie, Mishal (Institute of Infectious Disease and Molecular Medicine, 2018)
Tuberculosis (TB) is a leading cause of morbidity and mortality worldwide. People living with HIV are particularly susceptible to TB infection, and treatment of HIV-TB co-infection is challenging for multiple reasons, including potential drug-interactions. Drug-resistant TB is difficult to treat and is associated with high treatment failure rates, mainly because the antimycobacterial drugs currently available are ineffective against drug-resistant TB. Bedaquiline is a new antimycobacterial drug which has shown great promise through its excellent efficacy for treating drug-resistant TB. Being a new drug, however, potential drug interactions with antiretrovirals are a major concern. Bedaquiline is metabolized in the liver by an enzyme called cytochrome P450 3A (CYP3A). The antiretrovirals nevirapine, efavirenz, and lopinavir/ritonavir (LPV/r) can affect the activity of this enzyme, and consequently affect the concentration of bedaquiline in the patient's blood. Nevirapine and efavirenz increase the activity of CYP3A, which may result in increased metabolism of bedaquiline, thus decreasing the concentration of bedaquiline, with consequent risk of treatment failure or the further development of drug-resistance. LPV/r inhibits the CYP3A enzyme, which may result in decreased bedaquiline metabolism, thus causing high concentration of bedaquiline in the blood, with consequent risk of toxicity. We conducted a pharmacokinetic study in 43 adult patients with drug-resistant TB to evaluate the drug-interactions between bedaquiline and the antiretrovirals nevirapine and LPV/r. We did serial measurements of the bedaquiline concentration in their plasma over 48 hours, and compared these concentrations in patients who were on antiretroviral and those who were not on antiretrovirals. Our results showed that nevirapine had no significant effect on bedaquiline concentrations, while patients on LPV/r had bedaquiline concentrations 2 fold higher than patients not on antiretrovirals. We could not determine the clinical significance of this, but recommend that patients receiving LPV/r and bedaquiline in combination must be closely monitored for side-effects.